The epistemic and strategic dimension of the establishment of the IPBES: "epistemic selectivities" at work - Vadrot, Alice B.M. (Innovation (Abingdon, England), 2014)
The economic valuation of biodiversity and related market-based policy instruments are increasingly being referred to in the international politics of biodiversity and related Multilateral Environmental Agreements. They are both the subject of diverging interests, hence leading to conflict and critique, and an impetus for compromise on the way toward a "reasonable" solution to the environmental and economic crises. This development coincides with an extensive debate on how to increase the profile of biodiversity science and make it more policy relevant. This article takes a close look at decision-making processes leading to the establishment of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). Particular emphasis is placed on the implicit and explicit conflicts around the significance attached to the concept of ecosystem services within the IPBES debate. The article is based on the assumption that struggles over biodiversity knowledge become marginalized in favor of a stabilization of the "global paradigm of valorization." In this vein, the concept of ecosystem services contributes to sustaining the rationale that biodiversity can only be preserved if its diverse elements are commodified. This is theoretically underpinned by the concept of "epistemic selectivities," and I discuss its contribution to the understanding of the role of knowledge in institutional change.